Dietary macronutrients, endocrine functioning and intermediary metabolism in broiler chickens - Pair wise substitutions between protein, fat and carbohydrate - Malheiros, R. D.; Moraes, VMB; Collin, A.; Janssens, GPJ; Decuypere, E.; Buyse, J. (Elsevier B.V., 2003)
Three pens of male broiler chicks were raised under standard conditions and fed from 7 to 42 days of age three isocaloric diets each with 15.8; 19.6 and 19.5% of CP; and 51, 51, and 44% of CHO; and 6.5; 3.0 and 7.7% of fat, and designated as the low protein (LowCP), low lipid (LowL) and low carbohydrate (LowCHO) diets, respectively. Body weights and feed intake were monitored weekly and blood samples were collected at the same time for posterior analysis of hormone and metabolite content. Chickens fed the LowCP diet were characterized by a reduced body weight gain and feed intake and poorer feed conversion efficiency compared to those fed the LowL and LowCHO diets, which were very similar in this respect. Plasma corticosterone and glucose levels and creatine kinase activity were not significantly changed by diet composition. LowCP chickens were characterised by the lowest plasma T-4 and uric acid levels (indicative for reduced protein breakdown and lower protein ingestion) but highest plasma triglyceride levels (congruent with their higher fat deposition) compared to the LowL and LowCHO chickens. LowL chickens had on average higher plasma T-3 and free fatty acid levels compared to the LowCP and LowCHO chickens.In conclusion, a limited substitution of carbohydrate for fat in iso-nitrogenous, iso-energetic diets has no pronounced effects on plasma hormone and metabolite levels, except for the elevation in T-3 (may enhance glucose uptake) and free fatty acid levels in the plasma of the chickens fed the LowL diet. The protein content of the diet has a greater impact on zootechnical performance, and underlying endocrine regulation of the intermediary metabolism compared to the dietary lipid and CHO fraction. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: broiler chickens; dietary macronutrients; hormones; metabolites